Gingival papilla dimensions in anterosuperior regions adjacent to single-tooth implants - Perez, Fabiano [UNESP]; Segalla, José Cláudio Martins [UNESP]; Marcantonio, Élcio [UNESP]; Lauris, José Roberto Pereira; Ribeiro, João Gustavo Rabelo [UNESP]; Ferreira, Luciano Pedrin Carvalho [UNESP] (My University, 2012)
This study compared the dimensions of gingival papillae in anterosuperior areas presenting at natural teeth (teeth sites) or single-tooth implants adjacent to natural teeth (implant-tooth sites) by analyzing determined distances. A total of 45 teeth and 46 implant-tooth sites were carefully selected. Clinical evaluation consisted of visual and quantitative analyses with millimeter grids on radiographs. Implant-tooth sites showed a smaller gingival papilla dimension than tooth sites (P < .01). Both evaluated distances (contact point to bone crest and between the roots of adjacent teeth or implant platform to root of adjacent tooth) in all groups significantly influenced the presence/absence of gingival papillae (P < .01). © 2012 by Quintessence Publishing Co Inc.